Mechanistic examination of pre-exfoliating confinement of surface-active polystyrene nanobeads within pristine clay - Khvan, Svetlana; Kim, Junkyung; Lee, Sang-Soo (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2007)
Hydrophobic polymer (PS) nanoparticles preformed through an emulsifier-free emulsion polymerization method were successfully incorporated into a gallery of pristine sodium montmorillonite via interfacial cation exchange. The polymer beads confined between clay nanosheets were capable of (1) preventing the silicate layers from restacking and (2) maintaining the exfoliated state of clay. The increase in the abundance of surface groups promoted adsorption of the nanobeads onto the silicate surface and eventually led to the establishment of strong polymer-clay interactions. These findings suggest that, on the basis of the obtained pre-exfoliated clay masterbatch, the presence of strong polymer-clay interactions could improve the mechanical performance of nanocomposites. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: MODIFIED LAYERED SILICATES; X-RAY PHOTOELECTRON; EMULSION POLYMERIZATION; MELT INTERCALATION; NANOCOMPOSITES; MONTMORILLONITE